Impact of Tribulus Terrestris on male fertility: systematic review and meta-analysis - Fatemeh Goudarzi; Atiyeh Mohamadzadeh Vatanchi; Khadijeh Mirzaei Najmabadi (Mashhad University of Medical Sciences, 2019)
Introduction: Infertility is one of the most common problems in the world. In addition to recent attention to complementary drugs and alternative medicine for treatment of infertility, such as male infertility, the effect of some herbal medicines on sperm parameters has been studied. This systematic review and meta-analysis was conducted with aim to investigate the effect of Tribulus Terrestris on male fertility. Methods: In this systematic review, the databases of PubMed ،Web of science ، google scholar , Scopus , Cochrane, Sid , Magiran, and Iranmedex were searched using the keywords of "Tribulus Terrestris", "Fertility", "Infertility", "Oligo Azoospermia "and "Sperm parameters" without time and language limitation. All the articles published until 30 Nov 2017 were included in the study. Finally, nine articles were included that four articles were export in Meta-analysis process. Data were analyzed by comprehensive software (version 2). Cochran test and I2 index were used to assess the heterogeneity of the articles. Results: out of 1075 obtained articles, nine articles were entered to the systematic study that four article were export in Meta analysis process. The combination of data showed that the use of Tribulus Terrestris in men was accompanied by an increase in the parameters of sperm concentration and improved sperm morphology and sperm motility. Conclusion: Tribulus Terrestris is effective on the sperm parameters and sexual function in men and can be used as complementary medicine along with other treatments in infertility with male factors. Key words: